THE INFLUENCE OF ENTREPRENEURIAL SPIRIT, SELF-EFFICACY AND PERSONAL CHARACTERISTICS ON INTEREST IN ENTREPRENEURSHIP OF SULTAN ISKANDAR MUDA MEDAN HIGH SCHOOL - Alfriado Leonard Noprian Dolok Saribu; Afriani Mindo Dolok Saribu; Dahrul Siregar; Muhammad Yamin Siregar; Riza Fanny Meutia (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
The purpose of this study was to determine the entrepreneurial spirit, self-efficacy and personal characteristics on the interest in entrepreneurship in SMA sultan Iskandar muda medan. Methods of data collection using a questionnaire. Sampling with the slovin method. The results of this study indicate that the entrepreneurial spirit has a positive and significant effect on the interest in entrepreneurship in SMA sultan Iskandar muda medan. Self-efficacy has a positive and significant effect on the interest in entrepreneurship in SMA sultan Iskandar muda medan students. Personal characteristics have a positive and significant effect on the interest in entrepreneurship in SMA sultan Iskandar muda medan students. Simultaneously entrepreneurial spirit, self-efficacy and personal characteristics have a positive and significant effect on the interest in entrepreneurship in SMA sultan Iskandar muda medan students.